An Empirical Study For Sustainable Development Of The Fruit Processing Industries In One Of The Indian Suburbs (Journal of Namibian Studies : History Politics Culture, 2023)
Globalization has led to the surge of the food processing industries in many parts of the world. As a result, over the last two decades, several food processing industries have been established in several states in India. Of them, Fruit Processing Industries (FPIs) are one of the leading preferences among Indian industrialists and entrepreneurs, due to the wider availability of the various seasonal fruits. In this article, we analyze(based on empirical study) the new emerging forms of globalization and sustainable development of the FPI sin one of the suburbs (i.e., Dharmapuri district in Tamil Nadu) in India for the fruits such as Mango, Tomato, Guava, Sapodilla and Papaya and the corresponding processed products i.e., pulp, sauce, sugar, and citric acid etc. In addition to this, various factors in relation to the problems faced during production, exporting, as well as the problems confronted by the labors have been detailed analyzed using various statistical approaches.